PELUANG DAN TANTANGAN ASURANSI SYARIAH DI INDONESIA - Yuslinda (STAI Bahriyatul Ulum Pandan, Indonesia, 2024)
This research discusses the opportunities and challenges of sharia insurance in Indonesia. The research uses descriptive qualitative research with data collection techniques through literature studies, such as books, the internet, trusted websites and previous journals. The purpose of the research is to understand the opportunities and challenges of Sharia insurance in Indonesia. Therefore, the results obtained from the research prove that sharia insurance products continue to experience growth with strong positive encouragement from the community, where people benefit from sharia insurance. This is because there is a value of justice in Sharia insurance itself. Apart from that, the challenges faced by sharia insurance companies are that many people are completely unaware of the existence of sharia insurance, there are no strong regulations regarding sharia insurance, sharia insurance products are still modified from conventional insurance, small capital, and. Lack of HR (Human Resources). Therefore, it is very necessary for the government to play a major role in ensuring sharia insurance experiences optimal development and growth.